Kepemimpinan visioner kepala madrasah dalam meningkatkan mutu pendidikan - Subandi; Junaidah; Sarwati, Kemina; Hadiati, Eti; Mas Ayu, Sovia (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2022)
Visionary leadership is the ability to create and articulate a realistic, believable, and attractive vision for the future challenges of an organization that continues to grow and improve compared to today. Madrasah Aliyah Negeri Bandar Lampung shows a superior and quality madrasah. Of course superior and quality madrasas cannot be separated from the visionary leadership of the madrasa head. This type of research is descriptive qualitative in nature. Sources of research data include the head of the madrasa, deputy head of curriculum, teachers and students. Data collection techniques were carried out using interviews, observation, and documentation. The validity test of the data used is technical triangulation. The findings of this study include the role of visionary leadership as a determinant of direction, agent of change, spokesperson, and trainer or supporter in improving the quality of education in Madrasah Aliyah Negeri 1 Bandar Lampung.